(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
Because of its wide solubility range, Hydroxypropyl Cellulose (HPC) is suitable for fabricating fine-fiber materials via electrospinning. The resulting electrospun non-woven fabric (HPC-ESNW) requires an appropriate post-spinning treatment for applications in aqueous environments. In the present study, we examined the insolubilization of HPC-ESNW via cross-linking using bifunctional isocyanates. Modification of the fine-fiber surfaces with NCO groups enables introduction of cationic functionalities; we found that cationic Diethylaminoethyl (DEAE) groups are suitable for immobilization of aminoacylase- I onto these fine-fiber surfaces under mild conditions. The NCO groups can be also converted to amino groups, followed by activation with bifunctional N-hydroxysuccinimide (NHS) esters. The NHS-ESNW can chemically bind the aminoacylase-I. Two kinds of immobilized enzyme were tested for stereospecific recognition of a substrate and for immobilized activity yields. The results suggest that NCO-ESNW is a multi-purpose intermediate for chemical modification of ESNW and that the hydrophilic HPC-ESNW is a promising material for use as a matrix for enzyme immobilization.